Efektivitas Aplikasi Sikab Taji Prima Dalam Peningkatan Pelayanan Administrasi Kependudukan (ADMINDUK) Di Kabupaten Pacitan - Ahmad Isa Ansori; Eka Askafi (Otonomi, 2023)
Population Administration Document (Adminduk) is an important thing that every citizen must have. Adminduk documents include; KTP, KK, KIA, birth/death certificate, and moving/arrival letter. For the community, ownership of this Adminduk document can be related for increasing utilization of health services, opportunities to continue their education, open access to livelihood and economic sources, and guaranteed legal protection. For the government, complete and accurate of basic statistics of development based on Adminduk data are the basic capital for effective public service planning and budgeting. The purpose of this research is to describe: 1). Adminduk services before using application of SIKAB TAJI PRIMA, 2). problems and causal factors faced in Adminduk services, 3). Adminduk service improvement strategy, 4). The effectiveness of SIKAB TAJI PRIMA application in improving Adminduk services. The method used in this research is descriptive qualitative with data collection techniques in the form of interviews, observation and document study. The results of this research showed that: 1) Adminduk services before using the SIKAB TAJI PRIMA application were still not easy, not fast and not cheap, 2) the problem faced in previous Adminduk services was the problem of access to centralized service locations in the district 3) the main strategy for improving Adminduk services is; bringing services closer and using information technology, 4). The SIKAB TAJI PRIMA application has became effective in facilitating Adminduk services in Pacitan Regency. From this research it can be concluded that from various problems in Adminduk services and various innovations to improve services, the most effective innovation was found to be the use of the SIKAB TAJI PRIMA application. At least until the time this research was carried out, this application could be considered the fastest, easiest and cheapest as a medium for providing Adminduk services.